Bacterial nosocomial infections in a liver transplantation unit - Coelho, Júlio Cezar Uili; Parolin, Mônica Beatriz; Matias, Jorge Eduardo Fouto; Freitas, Alexandre Coutinho Teixeira de; Tolazzi, André Ricardo Dall’Oglio; Fragoso, Marta Francisca de Fátima; Castro, Maria Edutânia Skroski (Brazilian Journal of Transplantation, 2004)
Objective: The incidence of infection after liver transplantation remains high, being even higher if compared to other solid-organs transplantations. The aim of this study is to report the incidence, topographic distribution and the most frequently isolated microorganisms in nosocomial infections in our liver transplantation unit. Methods: medical charts of 1,963 patients admitted for liver transplantation or for pre or post transplantation complications were evaluated prospectively using the diagnostic criteria for nosocomial infections employed by the Center for Disease Control and Prevention (CDC) of the United States of America. During the period of time of the study, 175 liver transplantations were performed (148 with cadaveric donors and 27 with living donors). Results: nosocomial infections were diagnosed in 79 patients, representing 5.5% of the total patient admissions. The greatest incidence of infection was at the surgical site (27.7% - 30 cases), followed by pneumonia (20.3%), gastrointestinal infections (15.7%) and blood stream related infections (12%). The most common bacteria isolated in 79 positive cultures were: Staphylococcus sp (40.5%), Enterococcus faecalis (13.9%), Klebsiella pneumoneae and Escherichia coli (76% each). Among the infections caused by multiresistant bacteria (43% of the total), methicilin-resistant Staphylococcus aureus (MRSA) was the most prevalent (22 infections). The global mortality related to nosocomial infections was 22.7% (18 patients) and the most lethal infection was related to the bloodstream (30.7%). Conclusion: the most common site of bacterial infection in liver transplantation unit patients is surgical site infection and the most lethal infection is related to the bloodstream. The most frequent bacteria isolated were Staphylococcus sp and Enterococcus faecalis, being a great number of them multiresistent.